Treatment strategies for smartphone addiction: efficacy study of transcranial direct current stimulation and exergaming - Jun Chen; YuQing Jia; YanXia Zhu; Qin Liu; Fan Cheng; Bo Yang; EnMing Zhang; EnMing Zhang (Frontiers Media S.A., 2024)
ObjectiveSmartphone addiction is on the rise globally. This study aimed to compare the rehabilitative effects of transcranial direct current stimulation (tDCS) and exergames on smartphone addiction among college students. Additionally, we discussed the central mechanisms through changes in electroencephalography (EEG) to provide clinical insights.MethodsThirty-six participants were randomly assigned to three groups: control group, tDCS group (bilateral dorsolateral prefrontal cortex stimulation), and exergame group. The intervention lasted for 4 weeks with twice-weekly sessions. Outcome measures included the Smartphone Addiction Scale - Chinese Version (SAS-C), Iowa Gambling Task (IGT) net scores, and event-related potential (ERP) data collected during the IGT, focusing on P300 and feedback-related negativity (FRN) amplitudes.ResultsAll groups showed significant reductions in SAS-C scores post-intervention. Behaviorally, post-intervention scores improved, indicating significant effects of different interventions on participants' strategy choices. P300 amplitudes increased significantly at outcome electrode sites for all groups, with the most notable increase in tDCS group FC2 and CP1. FRN amplitudes decreased significantly post-intervention in the control and tDCS groups, with significant differences between the two groups.ConclusionAll three interventions appeared to have alleviating effect on smartphone addiction. After 4 weeks, participants showed improved executive control and decision-making abilities. Specifically, significant effects were observed in the tDCS group, with increased P300 amplitudes in the frontal, parietal, and central regions, as well as FRN amplitudes in the central and frontal regions. This suggested that tDCS enhanced psychological resources and improved inhibition control capabilities.